Level of Electronic Transparency of Peruvian Ministries - Navarro, Yulisa (2019)
This article increases information in electronic transparency. The main objective of this paper was to determine the transparency level of official web portals of the Peruvian ministries, as well as to uncover correlations between the levels of transparency, the type of ministry and / or the number of years past since the web portal has been working, or the gender of the responsible. In the first part of this work, I present a brief theoretical framework which establishes the principles of transparency regarding public information managed by the Peruvian State Administrative Entities. For this study two methodologies were used, the first one was the implementation of indicator’s table elaborated based on the Law of transparency for the collection and processing of data to obtain an objective diagnosis of the electronic transparency of the Peruvian Ministries, the second methodology was an correlation analysis, used to find those possible relationships between the variables chosen to be analyzed. The analysis allowed a diagnosis of the electronic transparency situation at ministerial level to 2017. As a main result, it was known which were the Ministries with the highest rate of compliance with the law for 2017 and also which are those that need more supervision to achieve their objective. The conclusion of the study was that, the Transparency Law has not yet been 100% implemented by more than 90% of the ministries.